The outcome of cataract surgery in eyes with end–stage glaucoma: Rezultati operacije sive mrene na očeh z glavkomom v zadnjem stadiju - Gračner, Tomaž; Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: To evaluate the outcome of phacoemulsification and intraocular lens implantation (PHACO IOL) in eyes with end–stage glaucoma.Methods: Eighteen eyes of 18 patients with end–stage glaucoma in which PHACO IOL was performed were included in this prospective clinical study. Intraocular pressure (IOP) was measured before and 1 week, and 1, 3, 6, and 12 months after PHACO IOL. The best corrected visual acuity (BCVA), the number of antiglaucoma medications and the visual field (VF) test results before PHACO IOL and at the end of follow–up were evaluated.Results: The follow–up period after PHACO IOL was 12 months for all eyes. The mean IOP before surgery was 13.5 mmHg (SD 2.6). There were no differences between the mean IOP measurements before and after surgery during the entire follow– up period (P>0.05). The mean preoperative BCVA was 0.65 (SD 0.3) logMAR, improving to a mean of 0.19 (SD 0.1) logMAR postoperatively (P
Keywords: Cataract surgery; end-stage glaucoma; outcome